The Problem of Organized Crime in the South American Tri-Border Area: Paraguay, Brazil and Argentina - Kosmynka, Stanisław (International Studies. Interdisciplinary Political and Cultural Journal, 2020)
The paper shows mechanisms and manifestations of the challenges for the security in the South American Tri-Border Area (Paraguay, Brazil and Argentina). It analyses the background of the activity of chosen organized crime and terrorist groups in this region. The article refers to some social and economic conditions for the spread of violence and illegal business in the area. It is focused on the most important dimensions of these problems and on the strategy implemented by South American governments to fight and prevent organized crime. The paper shows how the security forces deal with the threat and evaluate the impact of these efforts.